The Contribution of E-Training to Human Resource Development Case Study of Sonelgaz Foundation, Tebessa Branch - نصرة , نجوى; بوطرفة , صورية (Milev Journal of Research and Studies, 2023)
This research paper aims to clarify the importance of e-training in developing the skills of the workforce within the organization, and developing the attitudes and knowledge of these resources as the focus of the organization's activity. By determining its effectiveness in the organization's environment for the human resource. The study includes a sample from the Sonelgaz Foundation, Tebessa District. Through the distribution of a research form in data collection, it was processed with the program 22spss v. One of the most prominent results reached is that e-training affects the development of human resources, especially in the dimensions of knowledge, information development, and the development of attitudes.